2001
DOI: 10.1007/s102110100042
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic behaviour and control of access to hiding places in two intertidal blennies, Lipophrys pholis and Coryphoblennius galerita (Pisces: Blenniidae)

Abstract: In this study we investigated the relationships between dominance rank and access to shelters in captive groups of Lipophrys pholis and Coryphoblennius galerita, as well as the effects of group size and shelter availability. Dominance rank was strongly correlated with size in juvenile L. pholis and with sex and size in adult C. galerita, males being dominant over females of similar size. Access to shelters was significantly correlated with dominance rank. For both species, most interactions occurred out of she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The studies of other rocky intertidal fish suggest the same pattern (e.g. Almada et al, 1983;Mayr and Berger, 1992;Faria et al, 1998;Faria and Almada, 2001b). Although most studies have been done in captivity and may not be fully applicable to natural conditions, it is plausible that this wide spread agonistic behaviour may help dominant individuals to assure their right to occupy the most favourable sites in a given area, even though they do not occupy permanent territories.…”
Section: Factors That May Control Rocky Intertidal Fish Populationsmentioning
confidence: 87%
See 2 more Smart Citations
“…The studies of other rocky intertidal fish suggest the same pattern (e.g. Almada et al, 1983;Mayr and Berger, 1992;Faria et al, 1998;Faria and Almada, 2001b). Although most studies have been done in captivity and may not be fully applicable to natural conditions, it is plausible that this wide spread agonistic behaviour may help dominant individuals to assure their right to occupy the most favourable sites in a given area, even though they do not occupy permanent territories.…”
Section: Factors That May Control Rocky Intertidal Fish Populationsmentioning
confidence: 87%
“…This hypothesis would also explain the role of agonistic behaviour found in rocky intertidal fishes of many different families, which is present in juveniles and adults of both sexes without any obvious link to reproduction (e.g. Blennidae, Clinidae, Cotidae, Gobiidae, Gobiesocidae, Physidae, Pomacentridae, Sparidae, Tripterygidae) (for reviews see Gibson, 1969Gibson, , 1982Gibson, , 1986Gibson and Yoshiyama, 1999; additional information can be found in Mayr and Berger, 1992;Almada et al, 1996b;Gonc¸alves et al, 1996;Faria et al, 1998;Gonc¸alves and Almada, 1998;Faria and Almada, 2001b;Estabrook et al, 2002). This kind of behaviour, although very common in many rocky intertidal species, is absent or reduced in some other species (e.g.…”
Section: Factors That May Control Rocky Intertidal Fish Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the same study revealed that fish needed to reach a minimum size (TL ~ 19 mm) to begin the settlement process (Carvalho et al., ). After metamorphosis and settlement characterized by pronounced morphological and physiological changes, early juveniles show a typical behaviour associated with a benthic mode of life (Faria & Almada, ; Faria et al., ; Qasim, ). Recruitment of fishes <20 mm ceases 3 months after the end of the breeding season (Faria et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Rockpools also provide an ideal opportunity to study habitat partitioning in co‐occurring species, as rockpools are discrete spatial units with high numbers of quantifiable habitat variables (Metaxas & Scheibling 1993; Davis 2000). Mechanisms of resource partitioning in the rocky intertidal include differences in daily activity cycles (Davis 2001), seasonal cycles (Berger & Mayr 1992; Davis 2000), shelter sites (Faria & Almada 2001; Silberschneider & Booth 2001), dietary specialization (Szabo 2002) and vertical zonation (Raffaelli & Hawkins 1996; Zander, Nieder & Martin 1999). Out of these factors, vertical habitat partitioning has been found to be common among intertidal fishes (Zander et al .…”
Section: Introductionmentioning
confidence: 99%